"The Work I Do Matters": Cultivating a STEM Counterspace for Black Girls through Social-Emotional Development and Culturally Sustaining Pedagogies - Natalie S. King; Laura Peña-Telfer; Shaeroya Earls (MDPI AG, 2023)
Central to culturally sustaining pedagogy (CSP) is the notion that we sustain what we love by decentering the white gaze. Elevating CSP and the five core social-emotional learning competencies, we honed in on how Black and Brown girls developed knowledge and skills to manage their emotions, achieve goals, show empathy, and maintain healthy relationships within the context of a single-gender summer STEM program. These opportunities to engage in critical conversations to learn, unlearn, and relearn, while showing up as their full and authentic selves, are not often afforded in traditional STEM classes. This paper focuses on dialogue and interactions amongst four program participants-Samira, Rita, Brandy, and Joy. Critical discourse analysis was employed to challenge the dominance and reproduction of discourses by examining social contexts and systemic structures that they addressed in conversation. Findings revealed the importance of cultivating trusting and intentional learning spaces for Black and Brown girls to engage in open dialogue and critique oppressive discourses. It also displayed the significance of leaning into difficult conversations and pluralism to help adolescent girls realize the complexities of culture while also promoting joy and social-emotional development. Creating spaces that affirm Black and Brown girls matter; their contributions and work that they do matter.